Preparation method of soft and hard heterostructure porous carbon and application of soft and hard heterostructure porous carbon in supercapacitor

By using biomass and PET plastics to prepare soft and hard heterostructure porous carbon as supercapacitor electrode material, the problem of unsatisfactory cycling performance of electrode materials under high-quality loads is solved, and electrochemical performance with low leakage current, low self-discharge and high cycle stability is achieved.

CN119683626AActive Publication Date: 2025-03-25JILIN UNIVERSITY
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411884955.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing supercapacitor electrode materials have poor cycle performance under high-quality load conditions, serious leakage current and self-discharge phenomena, making it difficult to maintain excellent electrochemical performance.

Method used

Biomass and PET plastics are used as hard carbon precursors and soft carbon precursors respectively, and soft hard heterostructure porous carbon is prepared by carbonization and chemical co-activation methods, and used as high-quality load electrode materials for supercapacitors.

Benefits of technology

The prepared soft and hard heterostructure porous carbon materials have a high specific surface area, rich pore structure and improved conductivity, which significantly reduces leakage current and self-discharge phenomena, improves electrochemical performance, and exhibits excellent cycling stability especially under high-quality load conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683626A_ABST
    Figure CN119683626A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of soft and hard heterostructure porous carbon and application of the soft and hard heterostructure porous carbon in a supercapacitor, and belongs to the technical field of energy storage. The method comprises the following steps: pyrolyzing biomass in a tubular furnace to prepare biomass pyrolytic carbon, and taking the biomass pyrolytic carbon as a hard carbon precursor; the preparation method comprises the following steps: cutting PET into pieces, cleaning, pyrolyzing in a tubular furnace to prepare plastic pyrolytic carbon, and taking the plastic pyrolytic carbon as a soft carbon precursor; the preparation method comprises the following steps: mixing soft and hard carbon precursors according to a certain proportion, uniformly grinding, and preparing a soft and hard heterostructure porous carbon material through a chemical co-activation method; through optimization of experimental conditions, the structure and the property of the soft and hard heterostructure porous carbon are regulated and controlled, and the soft and hard heterostructure porous carbon is used as a high-quality loaded carbon electrode material to be applied to a supercapacitor. The defect engineering is effectively constructed through heteroatom self-doping, the acting force between electrolyte ions and the surface of the electrode is increased, and the wettability of the electrode material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energy storage, and specifically discloses a method for preparing soft-hard heterostructure porous carbon and an application thereof in a supercapacitor. Background Art

[0002] Biomass-based porous carbon and PET plastic-derived porous carbon have become an ideal supercapacitor electrode material due to their high carbon content and low cost. Biomass, as a thermosetting material, becomes an important precursor for the preparation of hard carbon materials after high-temperature carbonization. Hard carbon materials have a high degree of disorder and a large interlayer distance, which is conducive to the intercalation and extraction of ions. However, the low conductivity of hard carbon materials and the structural defects caused by the disordered structure lead to unsatisfactory cycle performance of supercapacitors. PET is a condensation product of terephthalic acid and ethylene glycol, and is collectively referred to as thermoplastic polyester together with PBT. After pyrolysis, cracking and other treatments, PET is an important source for the preparation of soft carbon materials. The interlayer arrangement of soft carbon is relatively orderly, and the high degree of graphitization has excellent conductivity. However, the low interlayer spacing and limited adsorption sites of soft carbon limit ion transport and thus reduce the electrochemical performance of the material. Therefore, the two porous carbon materials each have their own advantages and disadvantages. If the soft / hard carbon materials are composited, the synergistic effect between soft carbon and hard carbon will make up for their respective disadvantages and enhance the electrochemical performance of the composite material.

[0003] Patent reports on plastics are mostly used in automobile shells, biomedical engineering, construction engineering materials, etc., and there are currently no patent reports on the use of PET as a soft carbon precursor to prepare composite materials for energy storage. However, there are reports on patents for plastics in the field of energy storage, for example: Chinese patent document with publication number CN118744982A discloses a method for preparing carbon nanotubes using waste olefin plastics and waste carbon fibers as raw materials and its application in supercapacitors. And Chinese patent document with publication number CN118458765A discloses a method for preparing porous carbon of chlorine-containing plastics and its application. The above-mentioned prior art solutions all provide carbon materials derived from plastics for use in the field of energy storage, which provides an important reference for the high-value utilization of plastics, but the factors affecting their electrochemical properties are not elaborated in detail.

[0004] Laboratory research usually uses low-mass loaded electrodes, and the loading mass of active substances is usually 2-3 mg / cm 2 , low mass loading electrodes can show good electrochemical performance. However, for commercial applications, the mass loading of active materials needs to be increased to 10 mg / cm 2, can be used as an evaluation standard for its commercial application. There are relevant reports on patents for the preparation of high-quality loaded electrode materials. For example, the Chinese patent document with announcement number CN108292608B discloses supercapacitor electrodes and batteries with high active mass loading. Electrodes and batteries with high mass loading are prepared by increasing the specific surface area, pore structure, and thickness of the material, but the influence of the high mass loading structure on the electrochemical performance is not specifically elaborated. As the mass load increases, the electrode thickens, the ion transmission channel between the electrode active material and the electrolyte is extended, and the utilization rate of the active material decreases, resulting in an aggravation of the charge redistribution phenomenon. In addition, the obstruction of inactive materials such as current collectors and binders will also lead to a decrease in cycle stability, making it difficult to maintain excellent electrochemical performance in the case of thin electrodes, and the reduction of device performance is an inevitable phenomenon. Therefore, it is necessary to solve related problems by adjusting the microstructure of the electrode material. Summary of the invention

[0005] The purpose of the present invention is to address the problems existing in the prior art and propose a method for preparing soft and hard heterostructure porous carbon, using biomass and PET plastic as hard carbon precursors and soft carbon precursors respectively to prepare soft and hard heterostructure porous carbon by carbonization and chemical co-activation, and applying the soft and hard heterostructure porous carbon as an electrode material to a supercapacitor. The advantage of the present invention is that the prepared electrode material not only has a low content of oxygen-containing functional groups, but also exhibits excellent electrochemical properties when used as an electrode material for a high-quality loaded aqueous supercapacitor, especially slow leakage current, low self-discharge rate and high area capacitance.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] In the first aspect, a method for preparing soft-hard heterostructure porous carbon is proposed, comprising the following steps:

[0008] Step 1: crush the biomass raw material, remove impurities, and obtain biomass powder; cut the PET plastic into pieces and wash and dry them to obtain PET plastic pieces;

[0009] Step 2: placing the biomass powder and PET plastic fragments prepared in step 1 in a tube furnace respectively, pyrolyzing and carbonizing in an inert atmosphere, with a heating rate of 5°C / min, a carbonization temperature of 600°C, and a carbonization time of 1h, to obtain biomass pyrolysis carbon CHC and plastic pyrolysis carbon PHC respectively;

[0010] Step 3: The biomass pyrolysis carbon CHC and plastic pyrolysis carbon PHC prepared in step 2 are mixed in different proportions and then mixed with NaOH in a mass ratio of carbon to alkali of 1:2.5, and fully ground evenly. The mixture is heated to 750°C in an inert atmosphere in a tubular furnace for activation for 1 hour. After cooling to room temperature, the sample is taken out and washed with deionized water until it is neutral, and then placed in an oven and dried at 120°C to prepare a soft and hard heterogeneous porous carbon.

[0011] Furthermore, the biomass in step 1 includes one of chitosan, gelatin, rice husk, bamboo, and cotton.

[0012] Furthermore, the PET plastic in step 1 is shredded and then ultrasonically cleaned with anhydrous ethanol and deionized water, and dried at 50°C.

[0013] According to a specific embodiment of the present invention, in step 3, biomass pyrolysis carbon CHC and plastic pyrolysis carbon PHC are mixed in a mass ratio of 6:1.

[0014] According to a specific embodiment of the present invention, in step 3, biomass pyrolysis carbon CHC and plastic pyrolysis carbon PHC are mixed in a mass ratio of 4:1.

[0015] According to a specific embodiment of the present invention, in step 3, biomass pyrolysis carbon CHC and plastic pyrolysis carbon PHC are mixed in a mass ratio of 2:1.

[0016] According to a preferred embodiment of the present invention, in step 3, the biomass pyrolysis carbon CHC and the plastic pyrolysis carbon PHC are mixed in a mass ratio of 1:1.

[0017] In the second aspect, the soft and hard heterostructure porous carbon prepared by the above method is used as a high mass loading of 10-12 mg / cm 2 Carbon electrode materials are used in supercapacitors.

[0018] Preferably, the mass loading of the soft-hard heterostructure porous carbon is 11.3 mg / cm 2 .

[0019] Through the above technical solution, the present invention can bring the following beneficial effects:

[0020] 1. PET is a high molecular polymer, which is formed by esterification and polycondensation of terephthalic acid and ethylene glycol. The presence of ester bonds makes PET have good thermal stability, and the melting point is about 260℃. When PET is carbonized at high temperature, the molecular chain will break, isomerize, and the macromolecular organic matter will be converted into small molecular gas and liquid (oil) and coke, etc., forming PET pyrolytic carbon (PHC). Biomass contains active groups such as amino and hydroxyl groups. When carbonized at 600℃ for 1h, some C, H, O, and N will escape in the form of gas, and the heteroatoms will be relatively reduced, forming biomass pyrolytic carbon (CHC). The soft and hard heterogeneous porous carbon prepared by chemical co-activation of CHC and PHC has a higher heteroatom content, a larger specific surface area and a rich microporous structure. The introduction of PHC into CHC increases the mechanical properties of the soft and hard heterogeneous porous carbon, which is beneficial to improve the cycle stability of electrochemical energy storage devices.

[0021] 2. Compared with PET-derived soft carbon and biomass-derived hard carbon, the soft-hard heterostructure porous carbon prepared by the present invention improves the specific surface area of ​​the composite material through the synergistic effect between the short-range disordered hard carbon and the long-range ordered soft carbon, and the rich pore structure provides more adsorption sites for ion storage. At the same time, the conductivity, graphitization degree and mechanical stability of the soft-hard heterostructure porous carbon material are all improved, which is conducive to enhancing the electrochemical performance of the supercapacitor.

[0022] A further interesting effect is that the soft-hard heterostructure porous carbon is used as an electrode material in supercapacitors at a mass loading of 11.3 mg / cm 2 It exhibits excellent electrochemical performance: at a current density of 0.1A / g, the area capacitance is 3.72F / cm 2 The mass specific capacitance is 329.57F / g, the voltage retention rate is 78.29%, and the open circuit voltage decay rate is 21.85mV / h; after 10,000 constant current charge and discharge cycles at a current density of 1A / g, the capacitance retention rate is 94.14%. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0024] Figure 1 The leakage current and constant voltage charging time curves of soft and hard heterostructure porous carbon of different samples.

[0025] Figure 2This is a comparison chart of the rate performance of soft and hard heterostructure porous carbon of different samples.

[0026] Figure 3 This is a comparison chart of constant current charging and discharging of soft and hard heterostructure porous carbon of different samples.

[0027] Figure 4 This is a comparison chart of the area capacitance of soft and hard heterostructure porous carbon of different samples.

[0028] Figure 5 This is an impedance comparison chart of soft and hard heterostructure porous carbon of different samples.

[0029] Figure 6 This is a comparison chart of the cyclic stability of soft and hard heterostructure porous carbon of different samples.

[0030] Figure 7 This is the relationship between the energy density and power density of soft and hard heterostructure porous carbon of different samples.

[0031] Figure 8 This is the SEM image of CP-HPC-4 soft-hard heterostructure porous carbon;

[0032] Fig. 9 The flowchart is a method for preparing soft-hard heterostructure porous carbon. DETAILED DESCRIPTION

[0033] The invention puts biomass into a tubular furnace for pyrolysis to prepare biomass pyrolytic carbon, which is used as a hard carbon precursor; shreds and cleans waste plastic PET, and pyrolyzes it in a tubular furnace to prepare plastic pyrolytic carbon, which is used as a soft carbon precursor; mixes the soft and hard carbon precursors according to a set ratio and grinds them evenly, and prepares a soft and hard heterogeneous structure porous carbon material by a chemical co-activation method; and optimizes the experimental conditions to regulate the structure and properties of the soft and hard heterogeneous structure porous carbon, and uses it as a high mass loading (10-12 mg / cm 2 )Carbon electrode material, used in supercapacitors.

[0034] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention. In order to avoid confusing the essence of the present invention, well-known methods and processes are not described in detail.

[0035] Example 1

[0036] This embodiment provides a method for preparing biomass-based porous carbon, comprising:

[0037] The chitosan powder was placed in a tubular furnace filled with nitrogen atmosphere (chitosan itself has a certain heteroatom content, so no additional doping is required), heated to 600°C at a heating rate of 5°C / min, maintained for 1 hour, cooled to room temperature and ground to obtain biomass pyrolysis carbon CHC; the obtained CHC and NaOH were evenly ground in a mass ratio of 1:2.5, placed in a tubular furnace filled with nitrogen, heated to 450°C at a heating rate of 5°C / min and maintained for 30 minutes, continued to heat to 750°C and maintained for 1 hour, cooled to room temperature, washed with deionized water to neutrality, then added with a 1 mol / L HCl solution to soak for 1 hour, then washed with deionized water to neutrality, placed in an oven at 120°C for drying and grinding to obtain biomass-based porous carbon CHPC.

[0038] Example 2

[0039] This embodiment provides a method for preparing plastic-derived porous carbon, comprising:

[0040] The raw material PET plastic was cut into pieces, ultrasonically cleaned with anhydrous ethanol and deionized water, and dried in an oven at 50°C to obtain PET fragments; the obtained PET fragments were placed in a tubular furnace filled with nitrogen atmosphere, heated to 600°C at a heating rate of 5°C / min, maintained for 1 hour, cooled to room temperature and ground to obtain plastic pyrolysis carbon PHC; the obtained PHC and NaOH were evenly ground in a mass ratio of 1:2.5, placed in a tubular furnace filled with nitrogen, heated to 450°C at a heating rate of 5°C / min and maintained for 30 minutes, continued to heat to 750°C and maintained for 1 hour, cooled to room temperature, washed with deionized water to neutrality, then added with a 1 mol / L HCl solution to soak for 1 hour, then washed with deionized water to neutrality, placed in an oven at 120°C to dry and grind to obtain plastic-derived porous carbon PHPC.

[0041] Example 3

[0042] This embodiment provides a method for preparing a soft-hard heterostructure porous carbon, comprising:

[0043] The biomass pyrolytic carbon CHC in Example 1 and the plastic pyrolytic carbon PHC in Example 2 are mixed in a mass ratio of 6:1 and ground evenly to obtain a pyrolytic carbon mixture; the obtained pyrolytic carbon mixture and NaOH are ground evenly in a mass ratio of carbon-alkali ratio of 1:2.5, put into a tubular furnace filled with nitrogen, and heated to 450°C at a heating rate of 5°C / min and maintained for 30min, and then continued to heat to 750°C and maintained for 1h. After cooling to room temperature, it is washed with deionized water until neutral, and then a HCl solution with a molar concentration of 1 mol / L is added to soak for 1h, and then washed with deionized water until neutral, and then placed in an oven at 120°C for drying and grinding to obtain a soft and hard heterogeneous structure porous carbon CP-HPC-6.

[0044] Example 4

[0045] The biomass pyrolytic carbon CHC in Example 1 and the plastic pyrolytic carbon PHC in Example 2 were mixed in a mass ratio of 4:1, and other conditions were the same as in Example 3 to obtain a soft and hard heterogeneous porous carbon CP-HPC-4.

[0046] Example 5

[0047] The biomass pyrolytic carbon CHC in Example 1 and the plastic pyrolytic carbon PHC in Example 2 were mixed in a mass ratio of 2:1, and the other conditions were the same as in Example 3 to obtain a soft-hard heterogeneous structure porous carbon CP-HPC-2.

[0048] Example 6

[0049] The biomass pyrolysis carbon CHC in Example 1 and the plastic pyrolysis carbon PHC in Example 2 were mixed in a mass ratio of 1:1, and the other conditions were the same as in Example 3 to obtain a soft and hard heterogeneous structure porous carbon CP-HPC-1.

[0050] Example 7

[0051] The optimal mixing ratio of biomass pyrolysis carbon CHC and plastic pyrolysis carbon PHC is 4:1 by mass. On this basis, the prepared soft and hard heterogeneous porous carbon CP-HPC-4 is used as a high-quality loaded electrode material in supercapacitors. The present invention increases the mass loading of electrode materials to commercial levels and maintains good electrochemical performance.

[0052] Through N2 adsorption test, the best sample CP-HPC-4 has a specific surface area of ​​2710m 2 / g, micropores and mesopores account for 79.35% and 20.65% respectively. The high specific surface area can provide abundant active sites for the adsorption of charged ions. The micropore ratio is conducive to ion storage, and the mesopores are conducive to the rapid transfer of charged ions. The cooperation between micropores and mesopores demonstrates the efficient mass transfer advantage of CP-HPC-4. According to the resistivity of the four-probe powder resistivity test, the resistivity of CHPC, PHPC, and CP-HPC-4 are: 0.31Ω / cm, 0.19Ω / cm, and 0.25Ω / cm respectively. , The introduction of soft carbon enhances the conductivity of soft-hard heterostructure porous carbon. The present invention effectively constructs defect engineering through heteroatom self-doping, increases the interaction between electrolyte ions and electrode surfaces, and improves the wettability of electrode materials. The fine regulation of the above microstructure effectively reduces the leakage current and self-discharge problems of supercapacitors and improves the cycle stability of electrochemical energy storage devices.

[0053] Tables 1 and 2 show the electrochemical performance of samples of Examples 1 to 6. Tables 3 and 4 show the electrochemical performance of the sample of Example 7 at different mass loadings. Figure 1 The leakage current and constant voltage charging time curves of soft and hard heterostructure porous carbon of different samples are shown. Figure 2 A comparison chart of the rate performance of soft and hard heterostructure porous carbon of different samples is shown. Figure 3 A constant current charge and discharge comparison diagram of soft and hard heterostructure porous carbon of different samples is shown. Figure 4 A comparison of the area capacitance of soft and hard heterostructure porous carbon of different samples is shown. Figure 5 The impedance comparison diagram of soft and hard heterostructure porous carbon of different samples is shown. Figure 6 A comparison chart of the cyclic stability of soft and hard heterostructure porous carbon of different samples is shown. Figure 7 The relationship between energy density and power density of soft and hard heterostructure porous carbon of different samples is shown. Figure 8 The SEM image of CP-HPC-4 soft-hard heterostructure porous carbon is shown; Fig. 9 A flow chart of the preparation method of soft-hard heterostructure porous carbon is shown.

[0054] Table 1

[0055]

[0056] Table 2

[0057]

[0058] Table 3

[0059]

[0060]

[0061] Table 4

[0062]

[0063] Note: All electrochemical tests were performed in a two-electrode system with a KOH aqueous electrolyte concentration of 6 mol / L.

[0064] According to Tables 1 and 2, compared with biomass hard carbon and plastic-derived soft carbon, the leakage current and self-discharge of the soft and hard heterostructured porous carbon CP-HPC-X are slowed down. X is the ratio of CHC to PHC, X = 6, 4, 2, 1; with the introduction of soft carbon, the cycle stability and rate capability of heterostructured porous carbon are also improved.

[0065] According to Tables 3 and 4, after the best sample CP-HPC-4 was made into a high-quality load electrode, the leakage current was weakened, the open circuit voltage decay rate was reduced, and the cycle stability was improved compared to the low-quality load electrode. The soft and hard heterostructure porous carbon as an electrode material was applied to supercapacitors and showed good electrochemical performance.

[0066] The biomass of the present invention is not limited to chitosan, and may also be one of gelatin, rice husk, bamboo, cotton and the like.

[0067] In addition to PET plastic, the raw material of the plastic pyrolysis carbon of the present invention can also be polyethylene PE, polypropylene PP, polystyrene PS, polyester and the like.

[0068] In summary, the present invention provides a method for preparing soft-hard heterostructure porous carbon and its application in supercapacitors, which provides an innovative solution for high-value utilization of plastic waste and biomass waste. Through the synergistic effect of soft and hard carbon, the specific surface area of ​​soft and hard heterostructure porous carbon is increased, the degree of graphitization and mechanical stability of the material are enhanced; the leakage current and self-discharge of the supercapacitor are suppressed, and the electrochemical performance of the high-quality load supercapacitor is enhanced.

[0069] Obviously, the description of the above embodiments is only used to help understand the method of the present invention and its core idea, but for ordinary technicians in this field, various changes, modifications and substitutions can be made to these embodiments without departing from the spirit and principles of the present invention as described in the claims, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing soft-hard heterostructure porous carbon, characterized in that: The steps include: Step 1: crush the biomass raw material, remove impurities, and obtain biomass powder; cut the PET plastic into pieces and wash and dry them to obtain PET plastic pieces; Step 2: placing the biomass powder and PET plastic fragments prepared in step 1 in a tube furnace respectively, pyrolyzing and carbonizing in an inert atmosphere, with a heating rate of 5°C / min, a carbonization temperature of 600°C, and a carbonization time of 1h, to obtain biomass pyrolysis carbon CHC and plastic pyrolysis carbon PHC respectively; Step 3: The biomass pyrolysis carbon CHC and plastic pyrolysis carbon PHC prepared in step 2 are mixed in different proportions and then mixed with NaOH in a mass ratio of carbon to alkali of 1:2.5, and fully ground evenly. The temperature is increased to 450°C at a heating rate of 5°C / min and maintained for 30min, and then the temperature is increased to 750°C and maintained for 1h. After cooling to room temperature, it is washed with deionized water until neutral, and then a 1mol / L HCl solution is added to soak for 1h, and then washed with deionized water until neutral, and then placed in an oven at 120°C for drying and grinding to prepare a soft and hard heterogeneous porous carbon.

2. The method for preparing soft-hard heterostructure porous carbon according to claim 1, characterized in that: The biomass in step 1 includes one of chitosan, gelatin, rice husk, bamboo and cotton.

3. The method for preparing soft-hard heterostructure porous carbon according to claim 1, characterized in that: In step 1, the PET plastic is shredded, ultrasonically cleaned with anhydrous ethanol and deionized water, and dried at 50°C.

4. The method for preparing soft-hard heterostructure porous carbon according to claim 1, characterized in that: In step 3, biomass pyrolysis carbon CHC and plastic pyrolysis carbon PHC are mixed in a mass ratio of 6:

1.

5. The method for preparing soft-hard heterostructure porous carbon according to claim 1, characterized in that: In step 3, biomass pyrolysis carbon CHC and plastic pyrolysis carbon PHC are mixed in a mass ratio of 4:

1.

6. The method for preparing soft-hard heterostructure porous carbon according to claim 1, characterized in that: In step 3, biomass pyrolysis carbon CHC and plastic pyrolysis carbon PHC are mixed in a mass ratio of 2:

1.

7. The method for preparing soft-hard heterostructure porous carbon according to claim 1, characterized in that: In step 3, biomass pyrolysis carbon CHC and plastic pyrolysis carbon PHC are mixed in a mass ratio of 1:

1.

8. The hard-soft heterostructure porous carbon prepared by the method of any one of claims 1 to 7 is used as a high mass loading of 10-12 mg / cm 2 Carbon electrode materials are used in supercapacitors.

9. The mass loading of the soft and hard heterostructure porous carbon prepared by the method according to any one of claims 1 to 7 is 11.3 mg / cm 2 .

Citation Information

Patent Citations

  • Supercapacitor electrodes and cells with high active mass loading

    CN108292608B

  • Method for preparing carbon nano tube by using waste olefin plastic and waste carbon fiber as raw materials and application of carbon nano tube in supercapacitor

    CN118744982A

  • Preparation method of plastic-biomass active carbon and prepared active carbon thereof

    CN106865547A

  • Method for promoting low-temperature carbonization of waste polyester by using biomass

    CN110950318A

  • Method for preparing nitrogen-doped carbon material from biomass

    CN112194127A